Modelling within a thermodynamic framework : a footnote to Sanders (1999) - Nick Winder (Cybergeo)
Many modellers use micro-level dynamics to study aggregate behaviours. Since this approach was pioneered in physics, I call it "Thermodynamic modelling". I revisit Sanders’ comparison of synergetic with microsimulation methods and propose a new taxonomy of modellers. If "microsimulation modelling" is defined as "thermodynamic modelling with post-hoc alignment", then the synergetic and microsimulation paradigms are irreconcilable.